Rationally evaluating inconsistent theories - Weber, Erik; Van Dyck, Maarten (PHILOSOPHICA, 2012)
What happens if one applies the "evaluation methodology" of The Kuipers to inconsistent theories? What happens if one applies the "problem solving methodology" of Larry Laudan to inconsistent theories? We argue that in both cases something unacceptable happens. We show that application of Kuipers' methodology to inconsistent theories leads to a methodological stalemate: inconsistent theories are incomparable to consistent ones. Then we show that according to Laudan's methodology inconsistent theories are always better than consistent ones. Finally, we offer partial solutins to these problems.